Construction of S-scheme Bi2WO6/g-C3N4 heterostructure nanosheets with enhanced visible-light photocatalytic degradation for ammonium dinitramide - Lian, Xiaoyan; Xue, Wenhua; Dong, Shuai; Liu, Enzhou; Li, Hui; Xu, Kangzhen (Journal of hazardous materials, 2021)
Photocatalysis technology is considered as a promising environmental remediation strategy. Herein, photocatalytic degradation of ammonium dinitramide (ADN, main component of propellant) was investigated over Bi2WO6/g-C3N4 (BWO/CN) heterostructure nanosheets prepared by a one-step in-situ hydrothermal method. The operating conditions including ADN initial concentration, catalyst dosage, initial pH, temperature and green oxidizer (hydrogen peroxide) were optimized systematically. Under optimal conditions, the photocatalytic degradation rate of ADN over BWO/CN can reach 98.93% after 80 min visible-light irradiation. Besides, the composite has excellent stability for ADN treatment and nitrate ions are the major degradation products. Furthermore, S-scheme heterojunction mechanism was proposed to explain the extremely high REDOX performance of BWO/CN composite. [Display omitted] •Bi2WO6/g-C3N4 composites were fabricated by a hydrothermal method.•Photocatalytic degradation of ADN was investigated over Bi2WO6/g-C3N4.•The highest degradation rate reaches 98.93% under optimal conditions.•The main degradation products are nitrate ions.•S-scheme charge transfer mechanism was proposed.